The The Effect of Green Product and Perceived Price on Purchase Intention Through Green Perceived Value at BUMDes Maju Jaya, Kampar, Riau - Suci Hidayati; Gatot Wijayanto; Rika Promalessy (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Agricultural sector plays an important role in Indonesia’s economic development, particularly in supporting food security and rural livelihoods. However, excessive use of chemical fertilizers has led to soil degradation and environmental damage, encouraging the development of organic fertilizers as a sustainable alternative. Although organic fertilizers are more environmentally friendly and relatively affordable, their adoption among farmers remains low, indicating a gap between environmental awareness and actual purchasing behavior. Previous studies show that purchase intention toward green products is influenced by green product attributes and perceived price, but the findings remain inconsistent. In addition, limited research has examined green perceived value as a mediating variable in explaining farmers’ purchase intention, especially in the context of village-owned enterprises (BUMDes). Therefore, this study examines the effect of green product and perceived price on purchase intention through green perceived value in organic fertilizer produced by BUMDes Maju Jaya, Kampar, Riau.